Ethical tax decision-making: Evaluating the effects of organizational prestige valuations and tax accountants' financial situation - Holy Kwabla Kportorgbi; Francis Aboagye-Otchere; Teddy Ossei Kwakye (Cogent Business & Management, 2023)
This study investigates the interactive influence of two dimensions of perceived organizational prestige (POP) on ethical decision-making (EDM). The study also examines the moderating effect of the decision-maker's financial situation on the POP-EDM relationship. A Survey data from 356 tax accountants in two public-interest organizations were analysed using partial least square structural equation modelling. The study found that perceived external prestige (PEP) dimension of POP predicts EDM. Self-perceived prestige (SPP) dimension of prestige does not directly predict EDM but is a significant antecedent of PEP. Furthermore, decision-maker's financial situation does not moderate PEP-EDM relationship. The paper holds implications for image-building policies for public-interest organizations. Towards improving EDM, the paper recommends for organizations to focus on PEP-enhancing programs. This paper is foremost in establishing POP-EDM relationship. Further, the paper contributes to social identity theory by examining the EDM effect of both social identity motivations and potential ethical pressures on tax accountants.
Keywords: 650; Ethical decision-making; financial situation; social identity theory; tax accountants; organizational prestige